THE ANALISYS OF TERMINATION OF EMPLOYMENT AND UNEMPLOYMENT ON POVERTY IN INDONESIA - Firli Ariski; Umaruddin Usman; Tarmizi Abbas; Mariyudi Mariyudi; Safitri Safitri (Journal of Malikussaleh Public Economics, 2022)
This study aims to analyze the effect of Termination of Employment on Poverty in Indonesia. The data were analyzed using the method of Multiple Linear Regression (Ordinary Least Squares) and the analysis tool using the help of Eviews 10 software. Simultaneously, the variables of layoffs and unemployment affect poverty in Indonesia.